2013
DOI: 10.4103/2277-9531.107932
|View full text |Cite
|
Sign up to set email alerts
|

Medical records department and balanced scorecard approach

Abstract: Context:The Medical Records Department (MRD) is an important source for evaluating and planning of healthcare services; therefore, hospital managers should improve their performance not only in the short-term but also in the long-term plans. The Balanced Scorecard (BSC) is a tool in the management system that enables organizations to correct operational functions and provides feedback around both the internal processes and the external outcomes, in order to improve strategic performance and outcomes continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 4 publications
0
20
0
3
Order By: Relevance
“…21 of the implementations were performed in hospitals (2ry and 3ry HCOs) [41,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], and 15 in medical centers or health facilities (1ry HCOs) [30][31][32]48,[68][69][70][71][72][73][74][75][76].…”
Section: Settings Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…21 of the implementations were performed in hospitals (2ry and 3ry HCOs) [41,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], and 15 in medical centers or health facilities (1ry HCOs) [30][31][32]48,[68][69][70][71][72][73][74][75][76].…”
Section: Settings Differencesmentioning
confidence: 99%
“…The variation among BSC implementations in the categorization of the same KPIs reflects the need for data standardization. HCWs' training-related KPIs, for example, were categorized under the learning and growth perspective in almost half of the resulted studies [30][31][32][48][49][50][56][57][58][59][64][65][66][67][68][69][70][74][75][76][77]. Meanwhile the rest of studies categorized them under the perspectives of HCWs [69,76], quality [71], capacity for service, provision/service capacity [30,31,50,68,69,75], and health care facility functionality [32].…”
Section: Overall Completeness and Applicability Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Health care organizations differ from any other organizations as they need to balance efficiency, as well as balance cost against access, with quality and consumer outcomes (Inamdar and Kaplan, 2002). Nevertheless, since the early 1990’s, the BSC has been adopted by several health care organizations (Gurd and Gao, 2008; Zelman et al , 2003) as a means to improve quality, reduce inefficiencies, increase overall organizational effectiveness and maintain economic sustainability (Ajami et al , 2013). Gao and Gurd (2015) examined the diffusion and implementation of the BSC in China and found that linking it to a bonus structure is what makes the BSC prevalent in Chinese health care institutions.…”
Section: Overview Of the Bsc Literaturementioning
confidence: 99%
“…1,2 The most important tasks of MRD include supporting and protecting current and future care of the patient, official activities, continuous training programs, healthcare research, auditing and financial measures of the patients, efficiency management and risk management, service quality assurance, legal and quasi-legal requirements and all patient-related services. 3,4 Other tasks include:…”
Section: Introductionmentioning
confidence: 99%